2016
DOI: 10.2147/prbm.s91211
|View full text |Cite
|
Sign up to set email alerts
|

Insights into workplace bullying: psychosocial drivers and effective interventions

Abstract: Research on effectiveness of workplace bullying interventions has lagged behind descriptive studies on this topic. The literature on bullying intervention research has only recently expanded to a point that allows for synthesis of findings across empirical studies. This study addresses the question of whether workplace bullying can be reduced in prevalence and consequences, if so to what extent and by which strategies and interventions. It opens with a brief overview of the nature of bullying at work and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 54 publications
1
56
1
9
Order By: Relevance
“…Evidence that could inform future practice regarding what measures or interventions to implement to reduce bullying potentially derives from evaluated intervention studieshowever there is a dearth of such studies (Escartín, 2016;Hodgins et al, 2014;Vartia & Leka, 2011). Against this knowledge gap, our study provides important insights to understand what a bullying free organization would look like.…”
Section: Practical Implicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Evidence that could inform future practice regarding what measures or interventions to implement to reduce bullying potentially derives from evaluated intervention studieshowever there is a dearth of such studies (Escartín, 2016;Hodgins et al, 2014;Vartia & Leka, 2011). Against this knowledge gap, our study provides important insights to understand what a bullying free organization would look like.…”
Section: Practical Implicationsmentioning
confidence: 94%
“…Given the gravity of workplace bullying in society, for employers and employees alike, a striking paradox is that there is virtually no empirical evidence regarding the effectiveness of interventions to avert or reduce workplace bullying (see Escartín, 2016;Hodgins, MacCurtain, & Mannix-McNamara, 2014). Consequently, organizations largely focus on reducing workplace bullying through individual and interpersonal strategies, such as coaching and educational programs, to increase respectful behaviour and reduce conflict (Salin, 2008).…”
mentioning
confidence: 99%
“…They also had some clear differences, especially the study from Hoel and Giga [26], which probably was the most accurate intervention study stressed out by the recent review from Escartín [14]. This study added value to all the previous ones for several reasons:…”
Section: These Three Studies Have a Few Things In Commonmentioning
confidence: 98%
“…Previous scientific research has noticed that there is still a lack of empirical intervention studies and that unfortunately, most of the interventions developed in companies are not significantly successful. Nevertheless, a recent review found eight empirical intervention studies that accomplished good quality standards (i.e., studies had to be longitudinal (repeated measures) and had to actually apply an intervention strategy) that allowed several learning lessons [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the implemented interventions affected the bullying situation by bringing about a positive change in individual behaviour, attitudes, and self‐perception, along with improved knowledge (Escartín, ; Strandmark & Rahm, ). Notwithstanding, in other cases, bullying continued in spite of implemented interventions (Norton et al, ).…”
Section: Introductionmentioning
confidence: 99%